Market Based Organizational Learning - A study in the Indian Industry - Jayachandran, S. (Indian Journal of Marketing, 2007)
This research paper explores how Indian industries are sensitive to market-based learning. In line with Huber and Power’s (1985) guidelines for single informant, data were collected from 81 executives working in both public and private sector companies by administering a structured questionnaire. The analysis of data indicates that private sector companies are better learning oriented than public sector companies. Moreover, the analysis reveals that there is a significant positive correlation between market based learning orientation and overall performance.